People and Ideas in Medical Informatics - A Half Century Review - van Bemmel, J. H. (Yearbook of Medical Informatics, 2011)
Reviewing the onset and the rapid changes to make realistic predictions on the future of medical informatics.Pointing to the contributions of the early pioneers, who had their roots in other disciplines and by illustrating that from the onset an interdisciplinary approach was characteristic for our field.Some of the reasons for the changes in medical informatics are that nobody was able to predict the advent of the personal computer in the 1970s, the world-wide web in 1991, and the public start of the Internet in 1992, but foremost that nobody expected that it was not primarily the hardware or the software, but human factors that would be crucial for successful applications of computers in health care. In the past sometimes unrealistic expectations were held, such as on the impact of medical decision-support systems, or on the overly optimistic contributions of electronic health records. Although the technology is widely available, some applications appear to be far more complex than expected. Health care processes can seldom be fully standardized. Humans enter at least in two very different roles in the loop of information processing: as subjects conducting care - the clinicians - and as subjects that are the objects of care - the patients.Medical informatics lacks a specific methodology; methods are borrowed from adjacent disciplines such as physics, mathematics and, of course, computer science. Human factors play a major role in applying computers in health care. Everyone pursuing a career in biomedical informatics needs to be very aware of this. It is to be expected that the quality of health care will increasingly be assessed by computer systems to fulfill the requirements of medical evidence.
Keywords: Interdisciplinarity; pioneers in medical informatics; computer simulation; biosignal processing; electronic health records